PEMIKIRAN KI HADJAR DEWANTARA DALAM PERSPEKTIF HUKUM ISLAM - T, Marlini; BJ, Jusmiwarti; Saifullah, Saifullah; Julhadi, Julhadi; Asmaret, Desi (STKIP Pesisir Selatan, 2025)
This study examines the educational thoughts of Ki Hadjar Dewantara (KHD) from the perspective of Islamic law to reveal the common ground and its relevance. KHD, as a pioneer of Indonesian national education, offers a liberating educational philosophy, Tri Pusat Pendidikan, and Among System as well as the fundamental concept of Tri Nga concept of Tri Nga (Understand=know), (Feel=understand), (Nglakoni=do). On the other hand, Islamic law provides a universal value framework based on the Qur'an and Sunnah, with Maqashid Syariah as its main objective which includes the maintenance of religion, soul, mind, descendants, and property. Using the method of library research and comparative analysis. This study finds significant alignment between KHD's educational philosophy and the principles of Islamic law. The implication of the synthesis of these two thoughts is the development of a more integrative, innovative, and holistic model of Islamic education in Indonesia, capable of producing a generation that is intelligent, has noble character, is independent, and cares about society. This study contributes to interdisciplinary studies and provides practical guidance for the curriculum and practice of Islamic education.